Plant regeneration and cellular behaviour studies in celosia cristata grown in vivo and in vitro - Taha, Rosna Mat; Wafa, Sharifah Nurashikin (Hindawi Publishing Corporation, 2012)
Tissue culture studies of Celosia cristata were established from various explants and the effects of various hormones on morphogenesis of this species were examined. It was found that complete plant regeneration occurred at highest percentage on MS medium supplemented with 2.0 mg/L NAA and 1.5 mg/L BAP, with the best response showed by shoot explants. In vitro flowering was observed on MS basal medium after six weeks. The occurrence of somaclonal variation and changes in cellular behavior from in vivo and in vitro grown plants were investigated through cytological studies and image analysis. It was observed that Mitotic Index (MI), mean chromosome numbers, and mean nuclear to cell area ratio of in vitro root meristem cells were slightly higher compared to in vivo values. However, in vitro plants produced lower mean cell areas but higher nuclear areas when compared to in vivo plants. Thus, no occurrence of somaclonal variation was detected, and this was supported by morphological features of the in vitro plants.